Microwave‐assisted synthesis of MgH2 nanoparticles for hydrogen storage applications (2025)
ABSTRACT: Magnesium’s high storage capacity, with a theoretical value of about 7.6 wt.%, makes it a via- ble candidate for hydrogen storage. However, slow kinetics and strong thermodynamic stability lead to a rather high desorption temperature, usually above 350 °C. It has been demonstrated that nanosizing magnesium-based materials is a successful strategy for simultaneously improving the kinetic and ther- modynamic characteristics of MgH2 during hydrogen absorption and desorption. MgH2 nanoparticles were obtained by microwave assisted synthesis. To the best of our knowledge, synthesis of MgH2 nanoparticles by this method has not been reported. It was possible to produce MgH2 nanoparticles smaller than 20 nm. MgO and Mg(OH)2 were also present in the produced nanoparticles, although these compounds may enhance the processes involved in the release and absorption of hydrogen.